Evolutionary process of an organization of huerteros or vegetable gardeners in the province of Buenos Aires (Argentina): the case of the Cirujas Civil Association from La Matanza - Lombardo, Patricia (2024)
Due to the deepening of neoliberal policies in the 1990s, the labor market suffered changes that led to an increase in precariousness and unemployment, a drop in income, and an increase in poverty. In this context, the ProHuerta Program (Pro Vegetable Garden Program) was launched to facilitate access of the vulnerable population to a healthier and more diverse diet. In the district of La Matanza (province of Buenos Aires, Argentina), in 1996, some volunteer promoters of this program decided to create an association, the Cirujas Civil Association from La Matanza as an alternative organization, oriented to satisfy their needs and part of the Matanza community’s needs. The general objective of this study is to analyze the evolutionary process of this organizational experience as well as to understand its scope and contribution to community development. To this end, a case study was conducted following a qualitative approach.